Mobilization structures and political change in an authoritarian context: the national association for change as a case study (2010–2011). Issue 1 (2nd January 2020) - Magued, Shaimaa
ABSTRACT: In spite of the eruption of numerous public protests in contestation of the Hosni Mubarak regime since 2004, it was only with Khalid Said's death that public protests gained momentum. The torture to death of the young Alexandrian man by police officers incited rage among youth on social media where pictures of his disfigured face went viral. Although it was not an unprecedented case of violation, this study argues that Khalid Said's death was a transformative event that enabled Mohamed ElBaradei's National Association for Change to provide the necessary mobilisation structures for youth protests. The NAC mobilised opposition groups and movements, fuelled by a shared grievance over the death of Said, into protests calling for Mubarak's ouster. While the literature has mainly focused on how mobilisation structures would develop into a successful collective action in democratic regimes, this study introduces transformative events as the reason behind the success of mobilisation structures in an authoritarian environment. By perceiving a shared grievance among youth, who were highly identified politically with Mubarak's opponents, and capitalising on a political opportunity to call for the fall of authoritarianism, transformative events led to collective action. This study relies on a qualitative research methodology based on exhaustive semi-structured interviews conducted by the author with 25 NAC members from December 2011 until August 2012 in Cairo.